INTERAKSI TEKANAN PEKERJAAN DAN KOMITMEN PADA PERILAKU CYBERLOAFING KARYAWAN - Hunik Sri Runing Sawitri (Universitas Trisakti, 2012)
The aims of this study were to examine 1) the effect of work stressor and commitment to supervisor on employee cyberloafing; 2) the influence of work stressor on employee cyberloafing with commitment to supervisor as a moderating variable. Work stressors consist of role ambiguity, role conflict, and role overload. This study has some hypotheses, la) the role ambiguity has a positive effect on cyberloafing, lb) the role conflict has a positive effect on cyberloafing, and lc) the overload has a negative effect on cyberloafing; 2) the commitment to supervisor has a negative effect on cyberloafing; 3a) the effect of role ambiguity on cyberloafing is moderated by the employee commitment to supervisor, b) the effect of role conflict on cyberloafing is moderated by the employee commitment to supervisor, c) the effect of role overload on cyberloafing is moderated by the employee commitment to supervisor. Through purposive sampling method, 103 samples were taken from administrative employees of Sebelas Maret University. The employees have an internet access when do their task. Data analysis using hierarchical regression analysis shown that only hypothesis 2 was supported. The employee commitment to supervisor has a significant negative effect on cyberloafing. While work stressor has not effect on cyberloafing, and commitment to supervisor has not moderate the effect of work stressor on cyberloafing.Keywords: Work stressor, Role ambiguity, Role conflict, Role overload, Commitment, Cyberloafing